Gut health in European lobster - the gut microbiome as a health marker in offshore sea culture - Holt, C (University of Exeter, 2020)
The European lobster (Homarus gammarus) represents one of the United Kingdom’s most valuable fisheries. High market prices and a relatively limited fishery suggests that the species may be a good candidate for aquaculture and/or further stock enhancement. Disease is one of the biggest threats to the development and progression of sustainable aquaculture. However very little is known in regard to diseases of the European lobster. Therefore, better characterisation of potential pathogens is vital to prevent collapse of any future culture initiative. The community of microorganisms within the gut, referred to as the gut microbiome, is involved in key metabolic processes affecting host health and fitness and may serve as a key resource in reducing susceptibility to pathogenesis. Here we utilise a series of histological and molecular techniques to better characterise lobster disease and the lobster gut microbiome and assess the use of sea-based container culture (SBCC) as a means to culture the species and overcome the bottlenecks associated with traditional land-based culture (LBC). In assessing mortality of land-based larvae and egg clutches entering the hatchery, we first detected the abalone parasite Haliphthoros milfordensis. Histological and molecular characterisation of this parasitic oomycete confirm past suspicions that H. milfordensis and Halocrusticida noduliformans are one and the same, highlighting the lack of available information surrounding animal oomycete pathogens. To facilitate monitoring of the parasite and growth of the literature, we developed and tested general oomycete primers, targeting the 18S ribosomal small sub-unit (SSU) and revealed a wealth of oomycete diversity in freshwater, marine water and soil samples. Monitoring health of deployed juveniles in SBCC, we observed histological signs of viral infection. Genome characterisation and phylogenetic reconstruction revealed the virus to be a new member of the Nudivirdae. Thus, we discovered the first described clawed-lobster virus: Homarus ...